Incidence of respiratory syncytial virus infection in infants and young children referred to the emergency departments for lower respiratory tract diseases in Italy - Medici, M.C.; Arcangeletti, M.C.; Merolla, et al., R. (Acta Biomedica Atenei Parmensis, 2004)
Background: Respiratory Syncytial Virus (RSV) is the leading cause of emergency visits and hospitalization for acute lower respiratory tract infections (LRTI) in infants and young children worldwide. To collect specific epidemiological data on the incidence of RSV infection among infants referred to Emergency Departments (ED) for LRTI in a Mediterranean country, an Italian multicenter epidemiological surveillance program was established. Methods: Eight pediatric centers throughout Italy participated in this study. The study population included 272 children ≤4 years of age, admitted to the ED between October 2000 and April 2001 for respiratory problems that might be possibly related to LRTI. 152 children were 2 years of age. Data regarding medical history and physical examination were recorded for each child, whereas an immunoenzymatic RSV test (TestPack RSV®, Abbott) was performed on nasal and pharyngeal secretions. Results: Out of 272 tested children, 85 were positive for RSV. The peak of the RSV epidemic occurred in February, with an earlier start and end of the RSV season in the northern and central regions, compared to the southern regions. Major risk factors for RSV infection were younger age (p